The Role of Type 2 Innate Lymphoid Cells in Allergic Diseases - Zheng, Haocheng; Zhang, Yi; Pan, Jiachuang; Liu, Nannan; Qin, Yu; Qiu, Linghui; Liu, Min; Wang, Tieshan (Frontiers in Immunology, 2021)
Allergic diseases are significant diseases that affect many patients worldwide. In the past few decades, the incidence of allergic diseases has increased significantly due to environmental changes and social development, which has posed a substantial public health burden and even led to premature death. The understanding of the mechanism underlying allergic diseases has been substantially advanced, and the occurrence of allergic diseases and changes in the immune system state are known to be correlated. With the identification and in-depth understanding of innate lymphoid cells, researchers have gradually revealed that type 2 innate lymphoid cells (ILC2s) play important roles in many allergic diseases. However, our current studies of ILC2s are limited, and their status in allergic diseases remains unclear. This article provides an overview of the common phenotypes and activation pathways of ILC2s in different allergic diseases as well as potential research directions to improve the understanding of their roles in different allergic diseases and ultimately find new treatments for these diseases.